Ornithine enhances common bean growth and defense against white mold disease via interfering with SsOAH and diminishing the biosynthesis of oxalic acid in Sclerotinia sclerotiorum - Nehela, Yasser; Mazrou, Yasser S. A.; EL_Gammal, Nehad A.; Atallah, Osama; Abdelrhim, Abdelrazek S.; Kumar, Sumit; Ahmed, Temoor; Ali, Qurban; Makhlouf, Abeer H.; Hussain, Warda A. M. (Frontiers in Plant Science, 2025)
The necrotrophic fungal phytopathogen, Sclerotinia sclerotiorum (Lib.) de Bary, employs a multilayered strategy to infect a wide range of host plants. The current study proposed the diamine L-ornithine, a non-proteinogenic amino acid that promotes the synthesis of other essential amino acids, as an alternative management strategy to boost the molecular, physiological, and biochemical responses of common bean (Phaseolus vulgaris L.) against white mold disease caused by S. sclerotiorum. In vitro experiments showed that L-ornithine significantly inhibited the mycelial growth of S. sclerotiorum in a dose-dependent manner. Moreover, it markedly diminished the white mold severity under greenhouse conditions. Moreover, L-ornithine stimulated the growth of treated plants suggesting that the tested concentration of L-ornithine has no phytotoxicity on treated plants. Additionally, L-ornithine enhanced the non-enzymatic antioxidants (total soluble phenolics and flavonoids), the enzymatic antioxidants (CAT, POX, and PPO), and upregulated the gene expression of three antioxidant-associated genes (PvCAT1, PvSOD, and PvGR). Moreover, in silico analysis showed that the genome of S. sclerotiorum possesses a putative oxaloacetate acetylhydrolase (SsOAH) protein that is highly similar in its functional analysis, conserved domains, and topology with OAH from Aspergillus fijiensis (AfOAH) and Penicillium lagena (PlOAH). Interestingly, the addition of L-ornithine to the potato dextrose broth (PDB) medium significantly down-regulated the gene expression of SsOAH in the mycelium of S. sclerotiorum. Likewise, exogenous application of L-ornithine significantly down-regulated the gene expression of SsOAH in the fungal mycelia collected from treated plants. Finally, L-ornithine application significantly diminished the secretion of oxalic acid in the PDB medium as well as infected leaves. Collectively, L-ornithine plays a pivotal role in maintaining the redox status, in addition to boosting the defense responses of infected plants. The current study provides insights that may lead to innovative eco-friendly approaches for controlling white mold disease and mitigating its impact on common bean cultivation particularly, and other crops in general.